Cellular uptake of modified mRNA occurs via caveolae-mediated endocytosis, yielding high protein expression in slow-dividing cells - Claudia Del Toro Runzer; Shivesh Anand; Carlos Mota; Lorenzo Moroni; Christian Plank; Martijn van Griensven; Elizabeth R. Balmayor (Elsevier, 2023)
Nucleic acids have clear clinical potential for gene therapy. Plasmid DNA (pDNA) was the first nucleic acid to be pursued as a therapeutic molecule. Recently, mRNA came into play as it offers improved safety and affordability. In this study, we investigated the uptake mechanisms and efficiencies of genetic material by cells. We focused on three main variables (1) the nucleic acid (pDNA, or chemically modified mRNA), (2) the delivery vector (Lipofectamine 3000 or 3DFect), and (3) human primary cells (mesenchymal stem cells, dermal fibroblasts, and osteoblasts). In addition, transfections were studied in a 3D environment using electrospun scaffolds. Cellular internalization and intracellular trafficking were assessed by using enhancers or inhibitors of endocytosis and endosomal escape. The polymeric vector TransIT-X2 was included for comparison purposes. While lipoplexes utilized several entry routes, uptake via caveolae served as the main route for gene delivery. pDNA yielded higher expression levels in fast-dividing fibroblasts, whereas, in slow-dividing osteoblasts, cmRNA was responsible for high protein production. In the case of mesenchymal stem cells, which presented an intermediate doubling time, the combination vector/nucleic acid seemed more relevant than the nucleic acid per se. In all cases, protein expression was higher when the cells were seeded on 3D scaffolds.